The Gaia RVS Benchmark Stars. III. Confirmed and new high radial velocity stars from Gaia DR3 - Caffau, Elisabetta; Katz, David; Bonifacio, Piercarlo; Gómez, Ana; Lallement, Rosine; Sartoretti, Paola; Royer, Frédéric; Panuzzo, Pasquale; Spite, Monique; François, Patrick; Leclerc, Nicolas; Sbordone, Luca; et al. (Astronomische Nachrichten, 2025)
High-velocity stars are interesting targets to unveil the formation of the Milky Way. In fact they can be recently accreted from an infalling dwarf galaxies or they can be the result of a turbulent merging of galaxies. Gaia is providing the community a way to select stars for their kinematics and the radial velocity, one of the speed components, is derived from the Gaia RVS spectrum. High absolute radial velocity values are sensitive to be false positive. They are rare and as such they are more easily impacted than lower velocity stars, by contamination by very low SNR spurious measures. We here investigate a sample of 26 stars with Gaia absolute radial velocity in excess of 500 km/s with spectroscopic follow-up observations with UVES. For all but one star the extreme radial velocity is confirmed and these stars are all metal-poor and, as expected, enhanced in the \ α \ elements. The complete chemical inventory confirm the large star-to-star scatter for the heavy elements and their on average larger ratio over iron with respect to the Sun, in agreement with the literature.
Gesehen am 20.01.2026